2015
DOI: 10.1039/c4gc01959h
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable conversion of carbon dioxide: the advent of organocatalysis

Abstract: The conversion of carbon dioxide (CO 2 ), an abundant renewable carbon reagent, into chemicals of academic and industrial interest is of imminent importance to create a higher degree of sustainability in chemical processing and production. Recent progress in this field is characterised by a plethora of organic molecules able to mediate the conversion of suitable substrates in the presence of CO 2 into a variety of value-added commodities with advantageous features combining cost-effectiveness, metalfree transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
307
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 588 publications
(311 citation statements)
references
References 151 publications
1
307
0
3
Order By: Relevance
“…1,2,6 Despite the disadvantage of CO 2 having sluggish reactivity, recent work has unambiguously demonstrated that new opportunities may become available when proper catalytic methods are designed that help to improve the reactivity, selectivity and/or sustainability profiles of such processes. Among the most widely studied reactions in CO 2 catalysis is the formation of cyclic organic carbonates (COCs) [11][12][13][14][15][16][17][18] apart from their analogous and related linear carbonates 19 and poly(carbonates). [20][21][22] These COCs have been frequently associated with numerous applications involving them as non-protic solvents, precursors for poly(carbonate) synthesis, electrolyte solvents and more recently as useful intermediates in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,6 Despite the disadvantage of CO 2 having sluggish reactivity, recent work has unambiguously demonstrated that new opportunities may become available when proper catalytic methods are designed that help to improve the reactivity, selectivity and/or sustainability profiles of such processes. Among the most widely studied reactions in CO 2 catalysis is the formation of cyclic organic carbonates (COCs) [11][12][13][14][15][16][17][18] apart from their analogous and related linear carbonates 19 and poly(carbonates). [20][21][22] These COCs have been frequently associated with numerous applications involving them as non-protic solvents, precursors for poly(carbonate) synthesis, electrolyte solvents and more recently as useful intermediates in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…4 They can nd application as aprotic polar solvents, electrolytes for batteries and raw-materials for the preparation of polycarbonates. [3][4][5][6][7] Amongst the catalysts able to efficiently convert CO 2 and epoxides into the corresponding cyclic carbonates, ammonium, phosphonium and imidazolium salts deserve to be mentioned. 8 To achieve an easy recovery from the reaction mixture and reuse of the catalyst for multiple cycles, most of these salts were also heterogenized 9 on different supports.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In order to transform the energetically unfavourable CO 2 conversion into a feasible process, high energy starting materials should be selected in combination with an efficient catalyst. When oxiranes or oxetanes are employed as reactants, the synthesis of the corresponding ve or six membered cyclic carbonates can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some of them are toxic whereas less/non-toxic and eco-friendly organocatalysts such as ionic liquids and halide salts are generally only efficient at high temperature and pressure that favours their degradation [7] . In the last years, development of new bicomponent organocatalysts [8] combining the use of organic salt or ionic liquids with hydrogen bond donor activators such as phenolic derivatives [9] , (amino)alcohols [10] , carboxylic acids [11] , (fluoro)alcohols [12] , silanols [13] , has been proposed to fasten the coupling of CO2 with epoxides under mild conditions. The efficiency of these catalytic systems has been mainly investigated for the coupling of CO2 with model petro-sourced small organic molecules such as propylene oxide or styrene oxide.…”
Section: Introductionmentioning
confidence: 99%